2019
DOI: 10.1080/08927936.2019.1569903
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Research on Pet Ownership and Animal Interactions among Older Adults

Abstract: A pdf of this paper can also be downloaded without charge. Gold Open Access sponsored by WALTHAM™.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 150 publications
2
91
1
1
Order By: Relevance
“…Evidence suggests that two forms of human-animal interaction, pet ownership, and animal-assisted interactions (AAI), promote each of these aspects of health at some point in the human lifespan (10). A recent meta-analysis documented that the strongest evidence of benefits of HAI for older adults is from studies of AAIs (8). Animal-assisted therapy or the less structured animal-assisted activities may prevent or reduce depression, loneliness, and anxiety and optimize psychological health as well as encourage physical activity and promote physical and cognitive function (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that two forms of human-animal interaction, pet ownership, and animal-assisted interactions (AAI), promote each of these aspects of health at some point in the human lifespan (10). A recent meta-analysis documented that the strongest evidence of benefits of HAI for older adults is from studies of AAIs (8). Animal-assisted therapy or the less structured animal-assisted activities may prevent or reduce depression, loneliness, and anxiety and optimize psychological health as well as encourage physical activity and promote physical and cognitive function (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of pet ownership or regular interaction with others' pets on the health of older adults is less clear (8). Little is known about patterns of pet ownership or regular contact with others' pets in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous breeds of dogs and cats, which have a wide diversity of roles and are most commonly kept as companions [3,4]. The human-animal bond provides benefits with regard to mental health and physical well-being [1]. Working dogs are engaged as assistants to entertain, shepherd livestock, conduct search and rescue and detect illicit food, drugs and human trafficking [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent methodological review paper, Friedmann and Gee (2018) evaluated and discussed a variety of other HAI research approaches investigating pet ownership, brief interactions with animals, and animal-assisted activities/interventions. In their candid discussion, several limitations involved in this research are reported, some of which echo the concerns raised by others in this thematic issue (e.g., Gee & Mueller, 2019;Thorpe & Kelly-Moore, 2019). For ease of consideration and accessibility we present a consolidated list of recommendations for future research on HAI and human aging, based on the limitations and suggestions noted by the authors in this thematic issue:…”
Section: Limitations Of Previous Research Strategies and Recommendatimentioning
confidence: 82%